On history and liberty: the ‘revisionism’ of Bronisław Baczko - Baiao, Helder Mendes (Hybris, 2017)
The ‘Warsaw School of History of Ideas’ is the name given to a ‘revisionist think tank’ which was led by the historian Bronisław Baczko from 1956 to 1968 in Communist Poland. This group reunited scholars like Leszek Kołakowski or Krzysztof Pomian around questions related to political believes, theological conceptions or utopian thought. Expelled from the University, B. Baczko left Poland and seek shelter in Geneva where he became a Professor of history of Ideas and historiography. In his new home, he developed an original vision on Enlightenment and the French Revolution.